EFFECT OF YOGIC PRACTICES ON SELECTED BIOMECHANICALVARIABLES AMONG SCHOOL BOYS - S, Deepa; D, Rajalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the purpose was to investigate the effects of yogic practices on selected biomechanical variables among school boys. A random selection of 150 boys ranging in age from 14 to 17 years old was made amongst the boys at the Government Higher Secondary School, Melavalavu, Melur, Madurai District, and Tamil Nadu in India. Experimental group I (n=50), Experimental group II (n=50), and Control group (n=50) were selected from the selected subjects. The training programme was designed for twelve weeks and Experimental group I (Yogic Practices) some particular Asanas, such as Suryanamaskar, Pranayama, Meditation and Relaxation for five days a week and 60 - 90 minutes/day, Experimental group II (Yogic Practices) some particular, Asanas,--such as Suryanamaskar, Pranayama, Meditation and Relaxation for five days a week and 60 - 90 minutes/day,   and group III (n=50) acted as Control group which did not undergo any specific Yogic training programme other than their regular life style. Yoga practices are considered Independent Variables. As dependent variables, Anterior Average Trajectory, as an example of a physiological variable, and biomechanical variables are included. Tests were administered to measure the chosen variables.  After completing the yoga training program, a pre-test and post-test were administered. ANCOVA was used to analyze the collected data. The significance between paired adjusted means was tested using Scheffe's post-hoc method. Significant levels were set at 0.05. The study showed that biomechanical variables such as Anterior Average Trajectory, which was compared to the Control group, were significantly improved in the Experimental I and Experimental II.